Allergenic Properties and Molecular Characteristics of PR-1 Proteins - Wangorsch, Andrea; Scheurer, Stephan; Blanca, Miguel; Blanca-Lopez, Natalia; Somoza, María Luisa; Martín-Pedraza, Laura (Frontiers in Allergy, 2022)
Only a small fraction of proteins in plants and animals are classified as allergens. The allergenic properties are frequently attributed to certain functional characteristics of the proteins, such as a role in the plant defense against biotic and abiotic stress, to achieve the systematic acquired resistance. In line with this, eight members out of 17 functional pathogenesis-related (PR) protein families have been characterized as allergens. The present review summarizes the molecular features and allergenic significance of allergens of the PR-1 family. Not many allergens have been identified as belonging to this protein family, with most of them having a pollen origin, like mugwort or Bermuda grass. Molecular and structural features of allergenic PR-1 proteins are discussed and attributed to their IgE-reactive properties, clinical manifestation, and cross-reactivity among different foods and inhalants.